A comparison of virulence genes, antimicrobial resistance profiles and genetic diversity of avian pathogenic Escherichia coli (APEC) isolates from broilers and broiler breeders in Thailand and Australia. Issue 5 (2nd September 2020) - Thomrongsuwannakij, Thotsapol; Blackall, Patrick J.; Djordjevic, Steven P.; Cummins, Max L.; Chansiripornchai, Niwat
ABSTRACT : Avian pathogenic Escherichia coli (APEC) is the causative agent of colibacillosis resulting in economic losses in the poultry industry worldwide. A total of 168 APEC isolates, equal numbers from Australian and Thai broilers/broiler breeders, were identified and tested for their susceptibility to ten antimicrobial agents. Most of the Thai APEC isolates were multidrug-resistant (MDR) (60.7%) whilst Australian APEC isolates showed a MDR rate of just 10.7%. The Thai APEC isolates exhibited high resistance to tetracycline (TET) (84.5%), amoxicillin (AMX) (70.2%) and trimethoprim–sulfamethoxazole (SXT) (51.2%) whilst the Australian APEC isolates showed lower levels of resistance (TET 36.9%, AMX 29.8%, SXT 17.86%). The 34 Thai APEC and four Australian APEC isolates which were resistant to nalidixic acid were characterized for their carriage of mutations in the quinolone resistance determining region of gyrA, gyrB, parC and parE . While no mutations were detected in gyrB in the Thai isolates, the Ser83Leu and Asp87Asn substitutions in gyrA and Ser80Ile in parC were common ( n = 9/34). In regard to the Australian isolates, the Ser83Leu and Asp678Glu substitution in gyrA, Pro385Ala and Ser492Asn in gyrB and Met241Ile and Asp475Glu in parC were identified ( n = 3/4). Rep-PCR analysis of the 84 Thai and 84 Australian APEC isolates showed 16 main clusters that mostly contained isolates from both countries. Our results suggest that the emergence of MDR is a major concern for the Thai APEC isolates and that more prudent use of antimicrobial agents in Thai poultry production is required.